Partial Fractions: Prerequisites
Partial Fractions: Prerequisites
Partial Fractions: Prerequisites
Introduction
It is often helpful to break down a complicated algebraic fraction into a sum of simpler fractions.
For example it can be shown that x24x+7+3x+2
has the same value as x+21 3
+ x+1 for any value of x.
We say that
4x + 7 1 3
2
is identically equal to +
x + 3x + 2 x+2 x+1
and that the partial fractions of x24x+7+3x+2
1
are x+2 3
and x+1 . The ability to express a fraction as
its partial fractions is particularly useful in the study of Laplace transforms, of z-transforms, in
Control Theory and in integration. In this Block we explain how partial fractions are found.
The sum of the partial fractions is identical in value to the original algebraic fraction for any
value of x.
Key Point
A linear factor ax + b in the denominator gives rise to a single partial fraction of the form
A
ax + b
.
7x+10
Example Express 2x2 +5x+3
in terms of partial fractions.
Solution
Note that this fraction is proper. The denominator is factorised to give (2x + 3)(x + 1). Each
of the linear factors produces a partial fraction. The factor 2x + 3 produces a partial fraction of
A B
the form 2x+3 . The factor x + 1 produces a partial fraction x+1 , where A and B are constants
which we now try to find. We write
7x + 10 A B
= +
(2x + 3)(x + 1) 2x + 3 x + 1
We may now let x take any value we choose. By an appropriate choice we can simplify the
right-hand side. Let x = −1 because this choice eliminates A. We find
so that the constant B must equal 3. The constant A can be found by substituting other values
for x or alternatively by equating coefficients.
7x + 10 = (A + 2B)x + (A + 3B)
Comparing the coefficients of x on both sides we see that 7 = A + 2B. We already know B = 3
and so
7 = A + 2(3)
= A+6
Part (b) Multiply both sides by (3x + 2)(x − 1) to obtain the equation from which we can find
values for A and B.
Answer
1 1 1
= which equals
x2 + 2x + 1 (x + 1)(x + 1) (x + 1)2
the factor (x + 1) occurs twice. We call it a repeated linear factor. The repeated linear factor
A B
(x + 1)2 produces two partial fractions of the form x+1 + (x+1) 2 . In general, a repeated linear
2
factor of the form (ax + b) generates two partial fractions of the form
A B
+
ax + b (ax + b)2
This is reasonable since the sum of two such fractions always gives rise to a proper fraction:
A B A(ax + b) B x(Aa) + Ab + B
+ 2
= 2
+ 2
=
ax + b (ax + b) (ax + b) (ax + b) (ax + b)2
Key Point
A repeated linear factor (ax + b)2 in the denominator produces two partial fractions:
A B
+
ax + b (ax + b)2
Once again the unknown constants are found by either equating coefficients and/or substituting
specific values for x.
10x + 18 A B
2
= +
(2x + 3) 2x + 3 (2x + 3)2
Part (b) Multiply both sides through by (2x + 3)2 to obtain the equation which must be solved
to find A and B.
Answer
Part (c) Now evaluate the constants A and B by equating coefficients. Equating coefficients of
x gives
Answer
Equating constant terms gives 18 = 3A + B from which B = 3. So, finally, we may write
10x + 18 5 3
2
= +
(2x + 3) 2x + 3 (2x + 3)2
Key Point
A quadratic factor ax2 + bx + c in the denominator produces a partial fraction of the form
Ax + B
ax2 + bx + c
3x + 1 Ax + B C
= 2 +
(x2 + x + 10)(x − 1) x + x + 10 x − 1
Answer
To evaluate C we can let x = 1 which eliminates the first term on the right. This gives
1
4 = 12C so that C =
3
Equate coefficients of x2 and hence find A.
Part (b) Using the result that A = −1/3 substitute any other value for x or equate coefficients
of x to find B.
Answer
3x + 1 − 13 x + 73 1
7−x 1
Finally = 2 + 3 = +
(x + x + 10)(x − 1)
2 x + x + 10 x − 1 3(x + x + 10) 3(x − 1)
2
Example Admittance
Admittance, Y , is a quantity which is used in analysing electronic circuits. A
typical expression for admittance is
s2 + 4s + 5
Y (s) =
(s2 + 2s + 4)(s + 3)
s2 + 4s + 5 As + B C
2
= 2 +
(s + 2s + 4)(s + 3) s + 2s + 4 s + 3
so that
2
2 = 7C and so C=
7
Equating coefficients of s2 we find
1=A+C
so that A = 1 − C = 1 − 2
7
= 57 .
Equating constant terms gives 5 = 3B + 4C
µ ¶
2 27
so that 3B = 5 − 4C = 5 − 4 =
7 7
9
so B=
7
5
s2 + 4s + 5 7
s + 97 2
Finally Y (s) = 2 = 2 + 7
(s + 2s + 4)(s + 3) s + 2s + 4 s + 3
5s + 9 2
which can be written as Y (s) = +
7(s2+ 2s + 4) 7(s + 3)
2x + 4 6x2 + 13x + 2
(c) 2 , (d) 2
4x + 12x + 9 (x + 5x + 1)(x − 1)
Answer
Key Point
Solution
The fraction is improper because n = 2, d = 1 and so d ≤ n. Further, note that n − d = 1. We
therefore need to include an extra term: a polynomial of the form Bx + C, in addition to the
A
usual partial fractions. The linear term in the denominator gives rise to a partial fraction x+1 .
So
2x2 − x − 2 A
= + Bx + C
x+1 x+1
Multiplying both sides by x + 1 we find
DERIVE can be used to obtain the partial fraction expansion of both proper and improper frac-
x3 − 3x2 + 1
tions. For example to find the partial fraction version of (an improper fraction)
(x − 1)(x + 2)
simply key Author:Expression (x ∧ 3 − 3x ∧ 2 + 1)/((x − 1)(x + 2)). DERIVE responds
x3 − 3 · x 2 + 1
(x − 1) · (x + 2)
Now hit Simplify:Expand to obtain the Expand Expression box. Choose x as the Expansion
Variable and Rational in the Amount box. Hit the Expand button and DERIVE responds
19 1
− +x−4
3 · (x + 2) 3 · (x − 1)
It would be a useful exercise to check the partial fraction expansions of the many algebraic
fractions presented in this Block.
(d) Removing the brackets in the denominator we see that it has degree 3. The degree of the
numerator is 2 and so this fraction is proper.